Glucose depletion causes haploid invasive growth in yeast - Cullen, Paul J. (The National Academy of Sciences, 2000)
Haploid yeast invades solid agar in response to nutrient limitation. To decipher the cues that underlie invasion, we have developed a single cell invasive growth assay. Using this assay, as well as the traditional plate-washing assay, we show that invasive growth occurs in response to glucose depletion. In the absence of glucose (or other fermentable sugar), individual cells adopted a nonaxial budding pattern and elongated morphology within the first cell divisions, and invasion into the agar was observed in microcolonies containing as few as 10 cells. In support of this observation, we found that glucose suppressed the hyperinvasive growth morphology of STE11-4, pbs2, hsl7, and RAS2V19 mutations. In addition, removal of glucose from YPD medium caused constitutive invasion in wild-type cells. We tested glucose control proteins for a role in invasion and found that Snf1, a protein required for derepression of glucose-repressed genes, was required for invasive growth. The transcription factor Sip4, which interacts with Snf1 and is induced during the diauxic shift, had an inhibitory role on invasive growth, suggesting that multiple mechanisms are required for glucose depletion-dependent invasion.